2007
DOI: 10.31399/asm.cp.itsc2007p1011
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Thermally Sprayed Wear Protective Coatings Exposed to Different Abrasive Wear Conditions in Comparison to Hard Chromium Platings

Abstract: For deposition of protective coatings different coating techniques are available. Usually, detailed evaluation of various deposit types and materials is necessary for selection of the best suited coating for specific application fields and demands. Subject of this work are thermally sprayed functional coatings applied as wear (and corrosion) protective layers. Examination of different optimized thermal spray coatings, i.e. HVOF sprayed WC/Co(Cr) and Cr3C2/NiCr coatings, conventional flame sprayed and fused sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In previous works, a conic expansion nozzle was found to provide optimum particle acceleration. 26,27 The spray torch was machine mounted onto a robotic arm, and a consistent spray pattern was implemented. The transverse speed of the torch range was between 50 and 100 mm s − 1 , and the raster path across the substrate overlapped by at least one-half of the spray footprint diameter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous works, a conic expansion nozzle was found to provide optimum particle acceleration. 26,27 The spray torch was machine mounted onto a robotic arm, and a consistent spray pattern was implemented. The transverse speed of the torch range was between 50 and 100 mm s − 1 , and the raster path across the substrate overlapped by at least one-half of the spray footprint diameter.…”
Section: Methodsmentioning
confidence: 99%
“…[22][23][24] Process optimisation can be implemented by measurement of the inflight particle state, 25 such as surface temperature, velocity and diameter; and relating these parameters to the coating process parameters and properties. Previous research ha identified the interactions of process parameters, such as spray tance (standoff distance), oxygen/fuel ratio and the gun technology 23,24,26 in relation to DE and coating properties.…”
Section: Introductionmentioning
confidence: 99%
“…If the wear loss of different materials shall be compared, the volumetric material removal has to be calculated or measured (compare chapter "Optical 3D surface analysis"). For some thermal spray coating types, volumetric wear losses according to the ASTM G 65 wear test are given in Table 2 [30].…”
mentioning
confidence: 99%
“…The parameters of the test -grinding pressure, type and size of the abrasive material, corrosive medium, counter body material and test temperaturecan easily be adapted to specific demands. Although variations of the test design are not part of the standardization, this offers a wide range of real working conditions to be modelled [30]. DIN EN 1071-3 "Scratch Test".…”
mentioning
confidence: 99%